Cholecystokinin octapeptide reduces myocardial fibrosis and improves cardiac remodeling in post myocardial infarction rats. (August 2020) - Wang, Can; Zhang, Cuili; Wu, Dongdong; Guo, Lu; Zhao, Fali; Lv, Jinxin; Fu, Lu
Abstract: Background/Aims: Myocardial infarction (MI) increases myocardial fibrosis (MF) and subsequent cardiac remodeling. Cholecystokinin octapeptide (CCK-8) is expressed in cardiomyocytes and plays an important role in cardiovascular regulation. In this study, we intend to use a rat model of myocardial infarction to evaluate the effects of CCK-8 on myocardial fibrosis and cardiac remodeling. Methods: Male Sprague-Dawley rats were separated into 3 groups: sham operation, MI + NaCl, and MI + CCK-8. All rats were subjected to left coronary artery ligation to induce MI or sham operation and then treated with CCK-8 or saline for 28 days. After 4 weeks, echocardiography was performed to assess cardiac function and myocardial fibrosis was evaluated using H&E and Masson's Trichrome-stained sections. The levels of BNP, CCK-8 in the plasma of all rats were detected by ELISA; RNA sequencing (RNA-seq) analysis was also adapted to detect differentially expressed genes in myocardial tissues of each group. Myocardial expression of fibrosis markers was analyzed by western blotting, immunohistochemistry and qRT-PCR. Results: CCK-8 was demonstrated to improve left ventricular function and results of H&E staining, Masson's trichrome staining, immunohistochemistry and western blotting showed that CCK-8 attenuated MF. Gene expression profiles of the left ventricles were analysed by RNA-seq and validated by qRT-PCR. Cardiac fibrosis genes were downregulated by CCK-8 in the left ventricle. Significance: CCK-8 can alleviate fibrosis in the noninfarcted regions and delay the left ventricular remodeling and the progress of heart failure in a MI rat model.